2004
DOI: 10.1002/pola.20319
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of carbon dioxide and epoxide

Abstract: An erratum has been published for this article in J Polym Sci Part A: Polym Chem (2005) 43(4) 916.The alternating copolymerization of carbon dioxide and epoxide to produce polycarbonate has attracted the attention of many chemists because it is one of the most promising methodologies for the utilization of carbon dioxide as a safe, clean, and abundant raw material in synthetic chemistry. Recent development of catalysts for alternating copolymerization is based on the rational design of metal complexes, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
146
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(148 citation statements)
references
References 67 publications
1
146
0
1
Order By: Relevance
“…Inspired by the creative work of Inoue and coworkers in 1969, 1 researchers have strived to develop more efficient catalytic systems for the polycarbonate production. Thus, a lot of research work reviewed by Rokicki and Kuran, 2 Beckman, 3 Darensbourg, 4 Sugimoto and Inoue, 5 and Coates 6 has demonstrated that CO 2 can be copolymerized with a number of epoxides. As described therein, in most cases propylene oxide and cyclohexene oxide were selected as an epoxide resource.…”
Section: Introductionmentioning
confidence: 98%
“…Inspired by the creative work of Inoue and coworkers in 1969, 1 researchers have strived to develop more efficient catalytic systems for the polycarbonate production. Thus, a lot of research work reviewed by Rokicki and Kuran, 2 Beckman, 3 Darensbourg, 4 Sugimoto and Inoue, 5 and Coates 6 has demonstrated that CO 2 can be copolymerized with a number of epoxides. As described therein, in most cases propylene oxide and cyclohexene oxide were selected as an epoxide resource.…”
Section: Introductionmentioning
confidence: 98%
“…[5] Over the last decade the use of homogeneous catalysts has lead to a drastic increase in catalytic activities. [6][7][8] For the copolymerization of CO 2 and propylene oxide, salen complexes, especially of chromium [9,10] and cobalt [11][12][13] have come into focus. Yet, the highest activities for the alternating copolymerization of CO 2 and cyclohexene oxide so far have been reached by Coates' bdiketiminato (BDI) zinc complexes (see below).…”
Section: Introductionmentioning
confidence: 99%
“…glutaric acid) 28 have been reported. [29][30][31] Moreover, transition metal complexes based on zinc proved to be highly efficient and selective. In this context, Darensbourg et al developed zinc phenoxide catalysts, which exhibit high turnover capabilities for the copolymerization of cyclohexene oxide (CHO) and CO 2 .…”
Section: -23mentioning
confidence: 99%